Analisis Strategi Pemasaran Sales Generalis Produktif Dalam Penyaluran Kredit Mikro PT. Bank Mandiri KCP Kudus Alun Alun - Anwar, Rahita Nadya; H, AG. Sunarno; Sutono, Sutono (Syntax Literate, 2025)
This study analyzes the marketing strategies of Productive Generalist Sales (SGP) in microcredit distribution at PT Bank Mandiri KCP Kudus Alun-Alun. The study is based on Bank Mandiri’s strategic role as a state-owned bank distributing KUR and KUM loans to MSMEs, yet experiencing a decline in borrowers over the past five years. Using a qualitative descriptive method through interviews, observations, and documentation, the research employs SWOT analysis to identify internal and external factors affecting SGP performance. Findings show strengths in competitive credit products, experienced SGP staff, and strategic branch locations, while weaknesses include suboptimal digital promotion, inefficient outreach patterns, and relatively long disbursement processes. Opportunities come from government support, MSME market potential, and financial technology development, whereas threats include competition from fintech and rural banks, economic instability, and shifting customer preferences toward faster services. The resulting strategies include optimizing networks and flagship products (SO), strengthening brand image and fast services (ST), transforming promotions into digital platforms (WO), and enhancing SGP competence with product diversification (WT). The study concludes that the success of microcredit marketing strategies depends on leveraging internal strengths, external opportunities, technology-based innovations, and human resource capacity building. These findings contribute theoretically to SWOT-based microcredit marketing strategy models and provide managerial implications for improving Bank Mandiri’s credit distribution performance.